Exploring Gen Z'S Consumption and Perception of Educational Content on Tiktok Platform: A Qualitative Study in Vietnam Context - Duong Hoai Lan; Tran Minh Tung; Vo Thi Kim Oanh; Tran Thi Kim Cuc (Kurdish Studies, 2024)
This qualitative research investigates Generation Z's perceptions of educational content on TikTok in Vietnam. Using semi-structured interviews, the study examines how Gen Z consume and perceive TikTok's short-form videos, focusing on preferences, multimedia elements, and the platform's evolving role in education. Thematic analysis of qualitative data reveals that authenticity and relatability are crucial for engagement, with users favoring a casual and relatable tone. User-generated content, such as personal narratives and collaborations, enhances the sense of community. The study identifies specific educational content types, including quick tutorials, study vlogs, and bite-sized language lessons, as popular among Gen Z in Vietnam. Visual engagement through demonstrations and unique effects, coupled with auditory impact through music and narration, enriches the learning experience. Interactive elements like quizzes contribute to user engagement and community building. The findings provide practical insights for educators, content creators, and policymakers to tailor educational content for Gen Z, enhancing the educational landscape on social media. This research contributes to ongoing discussions on digital education, underlining the importance of adaptive strategies to meet the dynamic preferences of contemporary learners.